The present and future status of heavy neutral leptons. (1st February 2023) - Abdullahi, Asli M; Barham Alzás, Pablo; Batell, Brian; Beacham, James; Boyarsky, Alexey; Carbajal, Saneli; Chatterjee, Animesh; Crespo-Anadón, José I; Deppisch, Frank F; De Roeck, Albert; Drewes, Marco; Martin Gago, Alberto; et al.
Abstract: The existence of nonzero neutrino masses points to the likely existence of multiple Standard Model neutral fermions. When such states are heavy enough that they cannot be produced in oscillations, they are referred to as heavy neutral leptons (HNLs). In this white paper, we discuss the present experimental status of HNLs including colliders, beta decay, accelerators, as well as astrophysical and cosmological impacts. We discuss the importance of continuing to search for HNLs, and its potential impact on our understanding of key fundamental questions, and additionally we outline the future prospects for next-generation future experiments or upcoming accelerator run scenarios.